Stercorary aseptic peritonitis due to diastatic caecal perforation: computed tomography findings - Runza, G.; Nicastro, N.; D'Andrea, et al., A. (Acta Biomedica Atenei Parmensis, 2006)
Caecal perforation is a complication secondary to colon obstruction. It may present with insidious clinical features and may be associated with chronic constipation. The event may become severe due to the peritonitic development.We present a case of caecal perforation associated with sub-occlusive carcinoma of the left colon and hypotonic colitis caused by chronic lavative abuse, demonstrated with Computed Tomography.